The Design of Financial Policies in Corporate Spin-Offs - Mehrotra, Vikas; Mikkelson, Wayne; Partch, Megan (Review of Financial Studies, 2003)
We examine differences in financial leverage between parent and spun-off firms that emerge from corporate spin-offs. Our tests control for past financing choices and the costs of adjusting capital structure, factors that can obscure cross-sectional patterns among firms' target leverage ratios. We find that firms that emerge from spin-offs with more financial leverage have a higher cash flow return on assets, lower variability of industry operating income, and a greater proportion of fixed assets. The positive relation between profitability and the use of financial leverage, in a setting that is free of pecking order effects, is particularly important because it contrasts with existing evidence. Our results indicate that the ability to cover debt payments and default-related costs are important determinants of the use of financial leverage, as implied by the trade-off theory of capital structure. We find no evidence that managerial incentives or governance characteristics affect the difference in leverage ratios in firms that emerge from spin-offs.